A Language Construct for DMIs - Zorzo, A. F. (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2000)
Dependable Multiparty Interacion (DMI) has recently been introduced as a mechanism that provides reliable interaction between participants. Specifically, a DMI is a multiparty interaction mechanism that provides facilities for handling concurrent exceptions and assuring consistency upon leaving the interaction. This paper describes how the DMI mechanism can be added to a programming language.